THE IMPACT OF CYBERSPACE AND GLOBALIZATION ON THE FUTURE OF ARCHITECTURE: VISIONARY INSIGHT - Abdou, Adel A. (2020)
Rapid advancements in telecommunications and information technology are witnessed all over the world. Architecture, the applied art of building for people, is expected to alter in one way or another in response to the remarkable changes resulting from such developments. The objective of this study is to discuss how futuristic alternative scenarios of architecture can be drawn or highlighted by considering factors such as information technology (IT), globalization, and the resulting constraints. The Internet (i.e. cyberspace) revolution is emphasized and presented. Potential impacts on sample buildings and spaces are analyzed and a short-term visionary reflection put forward. It is becoming evident that cyberspace has begun to take over architecture from the interiors we live and work in. However cyberspace should not be perceived as a threat; as people in a society we need physical interaction, so buildings will still be required Furthermore, the future of architecture within the framework of IT cannot be separated from the future of architectural education. Architectural education is the key to a new architecture that interacts with science and IT without undermining local heritage.